Five Legal Maxims that play Basic Role in the Jurisprudence Knowledge of Islamic Law (In the Context of Al-mabsut by Sarakhsi) - Gurbanov, Anar (Scholarya Demo Journal of Ruby, 2018)
Islam developed a legal concept unlike other religions and improved it gradually as a legal system, especially during the times of mujtahids. The basic concepts of the general principle in Islamic law are the ones mentioned in the Quran and the javamiul-kalim in Sunnah. Investigation of the sacred topics through sources by the Islamic lawyers of this period, Fiqh opinions of mujtahid imams, their ijtihads, Fiqh basics, logic and linguistics, as a result of their research by the induction method, originated as the science of Al-Qawaid. The article provides general information about the five basic rules of Islamic jurisprudence, which play an important role as dalil (evidence) directly in formulating conclusions. After explaining all the rules, several examples are given from the book of the famous Islamic jurist Sarakhsi Kitab Al-Mabsut and information is given about the topics he used. The five rules stated in the article are as follows: “The result must correspond to the purpose of the case”, “Doubts do not eliminate the truth”, “Difficulties imply relief’, “Damage need to be eliminated”, “Customs have legal force (i.e., they are resorted to decision time) ”.